2016
DOI: 10.1007/s13355-015-0384-1
|View full text |Cite
|
Sign up to set email alerts
|

The clock gene period is essential for the photoperiodic response in the jewel wasp Nasonia vitripennis (Hymenoptera: Pteromalidae)

Abstract: This is not the published version. Please cite only the published version. この論文は出版社版でありません。引用の際には出版社版をご確認ご利用ください。 URI

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 38 publications
4
32
0
Order By: Relevance
“…These results, however, do not elucidate the role of period allelic variation. As we show here that variation in period correlates with variation in switch point for diapause induction, our results, combined with the study of Mukai & Goto (), strongly justify to further investigating the functional genetics behind the role of period allelic variation in adaptive photoperiodic diapause induction.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…These results, however, do not elucidate the role of period allelic variation. As we show here that variation in period correlates with variation in switch point for diapause induction, our results, combined with the study of Mukai & Goto (), strongly justify to further investigating the functional genetics behind the role of period allelic variation in adaptive photoperiodic diapause induction.…”
Section: Discussionsupporting
confidence: 78%
“…However, the per RNAi wasps were still able to induce diapause in their offspring when they were exposed to low temperature (which is known to trigger diapause). These results show that period affects the perception of the photoperiod, but is not involved in the maternal physiological mechanisms that lead to the production of diapausing offspring (Mukai & Goto ). These results, however, do not elucidate the role of period allelic variation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The regulation of seasonal photoperiodism is strongly related to the system governing circadian rhythms in insects (B€ unning, 1960;Goto, 2013;Dolezel, 2015). Recently, RNA interference approaches have demonstrated the role of some circadian clock genes in diapause expression of Nasonia vitripennis (Walker) (Mukai & Goto, 2016). In the pea aphid, Acyrthosiphon pisum (Harris), it has been demonstrated that the genes involved in the circadian rhythmsin particular per, Clock, cycle, and timelesswere also involved in the photoperiodic control of the induction of sexual morphs, that lay overwintering diapausing eggs (Cort es et al, 2010).…”
Section: Genetics Of Diapausementioning
confidence: 99%
“…In these cells, ‘clock genes’ such as period ( per ), timeless ( tim ), cycle ( cyc ) and Clock ( Clk ) are expressed and establish a few interlocked negative‐feedback loops (Tomioka & Matsumoto, ; Tataroglu & Emery, ). Several studies adopt gene silencing using RNA interference (RNAi) directed against clock genes, revealing their involvement in the photoperiodic responses (Sakamoto et al ., ; Ikeno et al ., , , , , ; Mohamed et al ., ; Meuti et al ., ; Mukai & Goto, ; Urbanová et al ., ; Kotwica‐Rolinska et al ., ). For example, Ikeno et al .…”
Section: Introductionmentioning
confidence: 99%